Comparing vowel hiatus resolution strategies in ChiHwesa and ChiManyika: an optimality theoretic account - Mvundura, Emaculate (Midlands State University, 2017)
The study makes a comparative analysis of how ChiHwesa and ChiManyika resolve vowel hiatal configurations. The dialects are against the VV sequence in structures and this triggers the application of the resolution strategies to break the vowel sequences. The comparative analysis was examined in the theoretical framework of optimality theory proposed by prince and Smolensky (1993), McCarthy and Prince (1999) and Kager (1999) which argues that constraints are universal and they belong to the grammar of every language. Its focus is centered on the ranking of constraints which are markedness constraints and faithfulness constraints. Data was analyzed to establish the phonological and morphophonological process which militates against hiatal configurations in both dialects. The key findings of the study revealed that the two dialects resolve hiatal configurations through coalescence, glide insertion/formation, vowel deletion or elision and epenthesis. The study recommends that the phonological and morphological systems of ChiHwesa and ChiManyika in the theoretical framework of the Optimality theory is necessary as means to understand the interaction of constraints.